2001
DOI: 10.1021/jf001273g
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and Dissipation of Ethofumesate and Halofenozide in Turfgrass and Bare Soil

Abstract: The effect of turfgrass cover on the leaching and dissipation of ethofumesate and halofenozide was studied. Sampling cylinders (20 cm diam. x 30 cm long) were placed vertically in plots of creeping bentgrass (Agrostis palustris Huds.), tall fescue (Festuca arundinaceae Schreb.), or bare soil. ethofumesate [(+/-)-2-ethoxy-2,3-dihydro-3,3-dimethylbenzofuran-5-yl methansulfonate] was applied at 840 g ai ha(-)(1) on September 21, 1997. Halofenozide (N-4-chlorobenzoyl-N'-benzoyl-N'-tert-butylhydrazine) was applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…In the case of halofenozide, Tomlin (2003) gives a half‐life of 3 to 77 d for turf. This suggests that the value of 64 d found by Gardner and Branham (2001a) may be close to the upper limit for turf half‐life and may have resulted from particular conditions occurring during the experiment (the authors mention that rainfall occurred shortly after application which moved the pesticide rapidly into the soil).…”
Section: Pesticide Dissipation Half‐lives For Turfmentioning
confidence: 66%
See 1 more Smart Citation
“…In the case of halofenozide, Tomlin (2003) gives a half‐life of 3 to 77 d for turf. This suggests that the value of 64 d found by Gardner and Branham (2001a) may be close to the upper limit for turf half‐life and may have resulted from particular conditions occurring during the experiment (the authors mention that rainfall occurred shortly after application which moved the pesticide rapidly into the soil).…”
Section: Pesticide Dissipation Half‐lives For Turfmentioning
confidence: 66%
“…First, turf foliage and thatch provide an environment that can sustain highly active microbial populations (Branham et al, 1993; Cole and Turgeon, 1978; Gardner and Branham, 2001a; Gardner et al, 2000; Horst et al, 1996). Raturi et al (2004) found that total microbial biomass carbon was, on average, 10 times greater in thatch than in the underlying soil.…”
Section: Pesticide Dissipation Processes In Turfmentioning
confidence: 99%
“…Morrica et al (2001) describes the kinetics of the chemical hydrolusis of imazosulfuron and evaluate the results to propose a degradation pathway. The mobility and dissipation of ethofumesate and halofenozide was studied in soils with and without turfgrass cover (Gardner and Branham, 2001). Ethofumesate leaching was reduced by 95% in the vegetated soil as compared to the bare soil.…”
Section: Fate and Transportmentioning
confidence: 99%
“…In bermudagrass and fallow systems, organic matter (OM) can bind pesticides (Weber and Keller, 1994; Gardner and Branham, 2001). Although OM accounts for only a small portion of soil, it has a large effect on both its biological and chemical properties.…”
mentioning
confidence: 99%
“…As a bermudagrass turf system ages, the thatch layer at the surface of the bermudagrass system thickens, and the lower portion of the thatch layer and soil below increase in OM content. In addition, the thatch layer in a turf system contains diverse populations of microorganisms that can degrade pesticides and can utilize root exudates and regular applications of fertilizer and irrigation for growth and metabolism (Gardner and Branham, 2001). In a fallow row crop system, however, OM is distributed uniformly in the plow layer (0–15 cm).…”
mentioning
confidence: 99%